Changes in Indices of Steatosis and Fibrosis in Liver Grafts of Living Donors After Weight Reduction - Choi, Jaehyuk; Choi, YoungRok; Hong, Su young; Suh, Sanggyun; Hong, Kwangpyo; Han, Eui Soo; Lee, Jeong-Moo; Hong, Suk Kyun; Yi, Nam-Joon; Lee, Kwang-Woong; Suh, Kyung-Suk (Frontiers in Surgery, 2022)
Background: A short-term weight reduction program for potential living donors was introduced to reduce the extent of hepatic steatosis prior to liver transplantation. We aimed to investigate changes in non-invasive hepatic steatosis and fibrosis indices among those who completed the program. Methods: Among 1,950 potential living liver donors between January 2011 and May 2019, 160 living donors joined the weight reduction program. The prospectively collected clinical data of these potential liver donors were analyzed retrospectively. Hepatic steatosis and fibrosis scores were determined using the fatty liver index (FLI), hepatic steatosis index (HSI), and NAFLD fibrosis score (NFS) and compared to MR spectroscopy (MRS) fat fraction results before and after weight reduction. Results: Thirty-nine potential living donors who had undergone MRS both before and after weight reduction were included in the analysis. Their body weight decreased from 78.02 ± 10.89 kg to 72.36 ± 10.38 kg over a mean of 71.74 ± 58.11 days. FLI, HSI, and MRS values decreased significantly from 41.52 ± 19.05 to 24.53 ± 15.93, 39.64 ± 3.74 to 35.06 ± 3.82, and 12.20 ± 4.05 to 6.24 ± 3.36, respectively. No significant decreases in NFS were observed. There was a significant correlation between the extent of HSI change and the extent of MRS change (R2 value = 0.69, P<0.001), although there was no correlation between MRS and FLI. Conclusion: The weight reduction program significantly improved non-invasive indices of hepatic steatosis over a short period. HSI may allow for prediction of simple decreases in hepatic steatosis.